(untitled) (Indian Journal of Arid Horticulture, 2025)
Emergence of industrial-scale Ziziphus fruits processing in the Mid‐Zambezi Valley necessitates selection of superior genotypes for cultivation to meet anticipated increased demand. The study evaluated morphological variation among Ziziphus fruits to determine their agronomic value and genetic diversity. Dry fruit samples were collected from bulked fruits and separated into three perceived varieties, which were further separated into 12 collections. Data depicted large coefficients of variation ≈50% for fruit and seed mass. Fruit parameters ranges were: mass (0.56–2.57 g), length (1.14–2.33 cm), width (1.05–2.16 cm), density (0.24–0.38 g/ cm3), percent pulp (63.03–89.28). Seed parameters were: mass (0.15–0.56 g), length (0.57–1.27 cm), width (0.43–0.66 cm). Fruit mass was positively correlated to yield components. Cluster analysis grouped the collections into two clusters with two sub‑clusters each. I concluded that there could be two Ziziphus species in the area. The WF‐variety is recommended for cultivation and further improvement because of its superior yield and taste variation. The HSDB variety is recommended for its high percent pulp subject to confirmation that hollowness is not a physiological disorder. Research is recommended to determine the Ziziphus spp. genotypes; genotypes nutritional composition; effect of ecology on fruit morphology; and evaluate agronomic performance.